THE STAGES OF ORGANIZING THE GERMAN LANGUAGE CLASS (L2) - Drăghici, Maria-Gabriela (International Journal of Research -GRANTHAALAYAH, 2020)
Learning German L2 is a challenge for fresh teachers, as the aspects they encounter in teaching are related to psycho-pedagogical factors, often difficult to manage. Most teachers prefer high-school teaching, considering that pupils are calmer and understand the notions taught faster than middle school or primary school pupils. However, we can say that all pupils, regardless of age, need a teacher who knows how to capture their attention in an engaging style. Teachers need to know that regardless of age, pupils are driven by affectivity and the role models they have in front of the class can positively influence their lives. Therefore, the constant training of the teacher is importer in order to properly manage the scientific principles in harmony with the psycho-pedagogical ones in teaching, learning and assessment in the classroom. Starting from the method of observation, our article deals with an essential topic of teaching German (L2) in primary school. But to observe the behavioral importance of teachers, we considered a total of 98 pupils from three 5th forms.